Why is History Didactics Needed in History (Non-pedagogic) Studies? - Šermukšnytė, Rūta (Lietuvos istorijos studijos, 2018)
[article in Lithuanian; abstract and key words in English] The purpose of this article is to answer the following question: why is history didactics needed in history (non-pedagogic) studies? The article begins with the existing definitions of the concepts of the didactics and history didactics as well as their statuses as academic disciplines. Further attention is paid to the German program of history didactics, an acquaintance with which has caused certain changes in the study programs at the Faculty of History of Vilnius University. The article concludes with a discussion of the reception of the German ideas in the studies of this faculty. The novelty of the article can be seen in the first attempt to scientifically legitimize the teaching of the history of didactics in history studies and to dispute the tradition, a popular one in Lithuania, of dissociating the research on teaching from the studies of historical consciousness, historical culture, memory etc. The article revealed that studies of history (non-pedagogy) can be substantially enriched by those history didactics that, with the help of the categories of historical consciousness and historical culture, treat history teaching (learning) as a part of daily communication and as an integral aspect of human life practice. Such a concept is typical of the German program of history didactics, associated with the 1960s and 1970s. The German program of history didactics was chosen as a theoretical basis when constructing the subject of history didactics for the Master’s Program in History (1997) of the Faculty of History in Vilnius University and when constructing the subject (later the module) of history didactics for the Bachelor’s Program in Cultural History and Anthropology (2003, 2012). German theory presents not only the framework for subject/module themes but it also serves as a theoretical basis that allows to conceptually combine the problems of historical consciousness, academic history, historical culture and school history. It is likely that the concept of history didactics, which goes beyond the school limits, will eventually return the consideration of conceptual issues to the discipline of Lithuanian history didactics.